Assuring data privacy with PRIVAS - a tool for data publishers - Miguel, Joana (2021)
The technology of nowadays allows to easily extract, store, process and use information about individuals and organizations. The increase of the amount of data collected and its value to our society was, at first, a great advance that could be used to optimize processes, find solutions and support decisions but also brought new problems related with lack of privacy and malicious attacks to confidential information. In this paper, a tool to anonymize databases is presented. It can be used by data publishers to protect information from attacks controlling the desired privacy level and the data usefulness. In order to specify these requirements a DSL (PrivasL) is used and the automatization of repository transformation, that is based on language processing techniques, is the novelty of this work.